An Investigation of the Influence of Various Shaped Cutouts on the Free Vibration Behavior of Sandwich Structures - Mutlu Tarık Çakır; Ufuk Demircioğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The current study deals with free vibration analysis of a sandwich beam in presence of different cutouts. PVC foam and glass fiber were used for the core and surface layers of the sandwich structures, respectively. First 6 frequencies of the sandwich structures were determined for different cutout shapes to see the effect of cutout shapes on the free vibration behavior of sandwich structures. For this, sandwich beams with different cutout shapes but with the same area were modeled. To see the effect of cutouts-shape only the shape of cutouts was changed and all other parameters were kept unchanged. Analyses were performed by using ANSYS apdl commercially available software. The analysis gives information about the influence of the cutout shape on the first six natural frequencies of the sandwich structures. From the results, it was observed that the changes of cutout shapes caused a significant decrease or increase in natural frequencies of sandwich structures beam depending on the cutout shape.